Assessment of Li ore to determine its amenability to processing for the extraction of lithium - Aylmore, Mark; Merigot, W.; Rickard, William; Spitalny, P. (2018)
With the impetus for less reliance on fossil fuels and cleaner environments, the ability to be able to extract lithium used in rechargeable batteries for portable electronic devices from ores economically, is essential. However a comprehensive understanding of the deportment of lithium and associated minerals in some ore bodies is limited. To facilitate further process development, a comprehensive understanding of the deportment of lithium and associated minerals in ore bodies is essential to allow the industry to predict the response of ore reserves to metallurgical treatment options. To quantify the different lithium bearing minerals in the ore, the chemistry and structure characteristics of a suite of Li mineral phases were examined and defined prior to examining ore material. The mineralogy, mineral associations and liberation characteristics of both ore-bearing and gangue minerals were characterised using a Tescan integrated mineral analyser and X-ray powder diffraction studies. The Li content and distribution within minerals were defined in both ore and mineral standards using Laser-ablation ICP-MS and FESEM with ToF-SIMS capabilities. The Al:Si ratio, Mn, Na, Fe and F contents were used to classify and group the different Li mica minerals. Analysis of a micaceous pegmatite from Lepidolite Hill showed the ore is predominately lepidolite composite particles, with moderate to minor amounts of liberated trilithionite, albite, quartz, polylithionite and muscovite. Minor amounts of topaz, elbaite and beryl also occur. The lepidolite particles consists of fine textured intergrowths of Li muscovite- muscovite, lepidolite, polylithionite and trilithionite. A calculated theoretical grade-recovery for minerals lepidolite and combined trilithionite and polylithionite indicated that optimum lithium bearing mineral recovery occurs in the sieve fraction −355 to +180 μm with rejection of quartz and albite that make up ~ 20% of the sample. However, further grinding of concentrated lepidolite to particle size <90µm would be required to breakup, concentrate and expose fine grains of polylithionite, trilithionite and possibly reject some muscovite before further treatment to extract lithium. Assessment of a lithium ore to determine its amenability to processing for the extraction of lithium.